Evaluation of e-Government Web Portals: The Case of Agricultural e-Government Services in Greece - Thomas Bournaris (Agronomy, 2020)
The evaluation of users’ satisfaction from the available e-Government services is a very important factor for the e-Government evolution. In this research, the MUlticriteria Satisfaction Analysis (MUSA) method and the related software is used in order to evaluate the users’ satisfaction of agricultural e-Government services. For this reason, we used the results of a survey conducted for an agricultural e-Government web portal in Greece. Five main criteria and the thirty-one sub-criteria were used in order to calculate the global and partial users’ satisfaction. From the results, the strong and the weak points of the agricultural e-Government services and the specific usability attributes that are more crucial for the users’ satisfaction were determined. The results of the questionnaire revealed that the average level of the users’ satisfaction is high but there are still actions to be taken in order to improve the provided agricultural e-Government services. Furthermore, the users of agricultural e-Government services attributed great importance to the criteria of interaction and accessibility. The MUSA method highlights the actions that have to be taken using action and improvement diagrams.